Brief Arabic tobacco craving questionnaire: An investigation into craving and heavy smoking in Saudi Arabian males - Abdulaziz A Albrithen; Edward G Singleton (Wolters Kluwer Medknow Publications, 2015)
Background and Objectives: Research in the United States has shown that craving tobacco is associated with smoking, yet no investigation has been done into the relationship between craving and the use of tobacco in Saudi Arabian smokers. The aim of this cross-sectional study was to examine the craving of tobacco by Saudi males and its influence on daily smoking. Subjects were recruited under the auspices of the Tobacco Control Program in Jeddah City and Riyadh. Methods: The American English version of the tobacco craving questionnaire (TCQ-12) is a valid measure of four distinct aspects (factors) of tobacco craving. The TCQ-12 was translated into Arabic tobacco craving questionnaire (ATCQ-12) and administered to a sample of 322 male smokers. Predictive validity was determined by examining the relationship between the factors and the number of cigarettes smoked per day (CPD). Results: In a general linear multivariate analysis of variance model, CPD increased significantly as either ATCQ-12 Factor 1 (emotionality) or Factor 3 (compulsiveness) increased. A significant Factor 1 by Factor 3 interaction indicated that Factor 1 was a better predictor of heavy smoking, but only when Factor 3 was low. Factor 3 was a better predictor of heavy smoking, but only when Factor 1 was low. Conclusions: The ATCQ-12 is a rapid measure of craving and valid predictor of CPD and heavy smoking. Craving in anticipation of smoking as relief from a negative mood (emotionality) is an indicator of psychological withdrawal symptoms, while craving in anticipation of the inability to control tobacco use (compulsiveness) is an indicator of physical dependence.